Paraṃpareya nakṣatragaḷu : Mādiga janaṅgada sāṃskr̥tika kathana - Lakṣmaṇ, 1957- (Beṅgalūru : Nirantara, 2010)
Collection of articles on history and cultural importance of Madigas community in Karnataka, India.
Includes bibliographical references.
In Kannada.
Keywords: Madigas -- India -- Karnataka; Dalits -- India -- Karnataka; India -- Social life and customs; Dalits; Madigas; Manners and customs; India; India -- Karnataka